2016
DOI: 10.5888/pcd13.160174
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity and Functional Limitations Among Adults 65 or Older, NHANES 2005–2012

Abstract: IntroductionThe development of functional limitations among adults aged 65 or older has profound effects on individual and population resources. Improved understanding of the relationship between functional limitations and co-occurring chronic diseases (multimorbidity) is an emerging area of interest. The objective of this study was to investigate the association between multimorbidity and functional limitations among community-dwelling adults 65 or older in the United States and explore factors that modify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
108
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(128 citation statements)
references
References 27 publications
(36 reference statements)
8
108
1
2
Order By: Relevance
“…Indeed, the overall prevalence of multimorbidity in our cohort was nearly 60%, which is only slightly lower than that recently reported for adults 65 years old and older (67%) without cerebral palsy, 22 and significantly higher than that reported for middle-aged men (40–49 years: 20.4%; 50–59 years: 38.1%) and women (40–49 years: 19.7%; 50–59 years: 35.8%) without cerebral palsy. 23 However, we caution the comparability between studies, because there is no current consensus on the number and type of conditions to be considered, the source of diagnoses, and the window of capture for chronic disease clustering.…”
Section: Discussioncontrasting
confidence: 82%
“…Indeed, the overall prevalence of multimorbidity in our cohort was nearly 60%, which is only slightly lower than that recently reported for adults 65 years old and older (67%) without cerebral palsy, 22 and significantly higher than that reported for middle-aged men (40–49 years: 20.4%; 50–59 years: 38.1%) and women (40–49 years: 19.7%; 50–59 years: 35.8%) without cerebral palsy. 23 However, we caution the comparability between studies, because there is no current consensus on the number and type of conditions to be considered, the source of diagnoses, and the window of capture for chronic disease clustering.…”
Section: Discussioncontrasting
confidence: 82%
“…Multimorbidity is often associated with functional limitation, reduced quality of life, higher mortality, polypharmacy and high treatment burden, higher rates of adverse drug events, and frequent use of health services [19,20]. The National Institute for Health and Care Excellence (NICE) [21] recommended that the multimorbidity approach should go beyond the benefits and risks of the guidelines for single health conditions, while focusing on the interaction between health conditions and treatment and their effect on quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review from 2015 concluded that multimorbidity predicts future functional decline in adults, but comparisons between studies are hampered by the heterogeneity in definitions and operationalizations of multimorbidity and functional decline and the included cohort studies had short follow-up time (1-3 years) [9]. Later studies including four cross-sectional and two cohort studies with 1 and 2 years follow-up time have also found associations between multimorbidity and ADL/IADL disability [34][35][36][37][38]. It may seem that disease combinations including depression and cognitive impairment increase the risk for ADL/IADL disability substantially compared to combinations of only somatic disease [37,39].…”
Section: Discussionmentioning
confidence: 99%